Clinical presentation, management, in‐hospital and 90‐day outcomes of heart failure patients in Trivandrum, Kerala, India: the Trivandrum Heart Failure Registry. (23rd May 2015) - Harikrishnan, Sivadasanpillai; Sanjay, Ganapathi; Anees, Thajudeen; Viswanathan, Sunitha; Vijayaraghavan, Govindan; Bahuleyan, Charantharayil G.; Sreedharan, Madhu; Biju, Ramabhadran; Nair, Tiny; Suresh, Krishnan; Rao, Ashok C.; Dalus, Dae; et al.
<x xml:space="preserve">Abstract</x> Objective To evaluate the presentation, management, and outcomes of patients hospitalized for heart failure (HF) in Trivandrum, India. Methods The Trivandrum Heart Failure Registry (THFR) enrolled consecutive admissions from 13 urban and five rural hospitals in Trivandrum with a primary diagnosis of HF from January to December 2013. Clinical characteristics at presentation, treatment, in‐hospital outcomes, and 90‐day mortality data were collected. 'Guideline‐based' medical treatment was defined as the combination of beta‐blockers, angiotensin‐converting enzyme inhibitors or angiotensin receptor blockers, and aldosterone receptor blockers in patients with left ventricular systolic dysfunction (LVSD). Results We enrolled 1205 cases (834 men, 69%) into the registry. Mean (standard deviation) age was 61.2 (13.7) years. The most common HF aetiology was ischaemic heart disease (IHD) (72%). Heart failure with preserved ejection fraction (≥45%) constituted 26% of the population. The median hospital stay was 6 days (interquartile range = 4–9 days) with an in‐hospital mortality rate of 8.5% (95% confidence interval 6.9–10.0). The 90‐day all‐cause mortality rate was 2.43 deaths per 1000 person‐days (95% confidence interval 2.11–2.78). Guideline‐based medical treatment was given to 19% and 25% of patients with LVSD during hospital admission and at discharge, respectively. Older age, lower education, poor ejection fraction, higher serum creatinine, New York Heart Association functional class IV, and suboptimal medical treatment were associated with higher risk of 90‐day mortality. Conclusion Patients hospitalized with HF in the THFR were younger, more likely to be men, had a higher prevalence of IHD, reported longer length of hospital stay, and higher mortality compared with published data from other registries. We also identified key areas for improving hospital‐based HF medical care in Trivandrum.